Bibliography of Periodicals Published in Ankara: 1923-2015 - Nilay Cevher (Türk Kütüphaneciliği)
This book which involves bibliography of all periodicals published in Ankara between 1923-2015 forms a basis for researchers who want to do sceintific studies about Ankara or periodicals published in Ankara. The book is formed of four main chapters. The first chapter is Preface written by Prof. Dr. Bülent Yılmaz who is also the first author of the book. The second chapter is a general evaluation about the statistical data about periodicals published in Ankara between 1923-2015. It includes three sub-chapters: Introduction, Evaluation and Conclusion. In the third chapter which is called Bibliography of Periodicals’ Names, the bibliography of 8798 periodicals are presented. And the last chapter is Subject Index. The book is a result of hard and disciplined work.